Imágenes que cuentan : iconotextos e historiografía para la arquitectura moderna - Molinos, Rita (2016)
This thesis can be understood, synthetically, as a development that:\n* studies the functions of printed images and the relationships between visual strategies and the historiographic script, in three books on the history of modern architecture, with original versions published in 1941, 1950 and 1960; successively reprinted and reissued. These are the works (cited respectively, according to those first editions): Sigfried Giedion, Space, Time and Architecture: The Growth of a New Tradition (Cambridge, MA: Harvard University Press), Bruno Zevi, Storia della Architettura Moderna (Turin: Enaudi) and Leonardo Benévolo, Storia della Architettura Moderna (Rome-Bari: Laterza);\n* observes the divergences between the three stories considering what has been raised by recent historiographical reviews regarding the differences between their authors and raises the problem of narrative differences at the level of the images is raised, as a new issue;\n* observes the images and graphic strategies as an alternative entryway for an intensive, denatured and disaggregated reading, where the visual contents can be indicative keys towards the interpretation of the three successive stories;\n* also understands that these books formed a set that stimulated the perception and diffusion of the doctrinal and the canonical and that resulted in a Modern Movement. In the duration of its biblio-historiographical construction, these differences were flattened, remaining unnoticed or forgettable for the reading public in the face of what -it was supposed- they coincided;\n* responds to a series of general questions raised from the recognition of the communicative importance of a profuse but not unlimited set of photographs, diagrams, tables and figures present in these successful products of disciplinary print culture. To what extent are their textual discourses or can they be understood exclusively independent of what the iconographic contribution implies? and What do these repertoires of images add?; How do they deviate -if they do- the meaning of the texts? And, from the historiographic order, it is posed what singular and successive distinctions do these illustrated stories offer, and how can they be understood as an accumulated set of the canonical aspects of the Modern Movement?;\n* It is assumed as an advance in the sense proposed by historiophoty, a subfield of narrative historiography, which combines narrative, history, image and medium in its subject matter. From this perspective, it proposes an observation of the functions of communication as units of the corpus and as an iconotextual genre for these stories, providing theoretical and methodological aspects applicable to future research.